2019
DOI: 10.1016/j.jim.2019.01.005
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of different indirect ELISAs for MERS-CoV serological testing

Abstract: Since 2012, MERS-CoV has caused up to 2220 cases and 790 deaths in 27 countries with Saudi Arabia being the most affected country with~83.1% of the cases and~38.8% local death rate. Current serological assays such as microneutralization (MN), plaque reduction neutralization, immunofluorescence, protein microarray or pseudoparticle neutralization assays rely on handling of live MERS-CoV in high containment laboratories or need for expensive and special equipment and reagents and highly trained personnel which r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
42
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3

Relationship

5
3

Authors

Journals

citations
Cited by 32 publications
(45 citation statements)
references
References 31 publications
3
42
0
Order By: Relevance
“…84 Several diagnostic tests are under development to accelerate turnaround times from sample analysis to result. [85][86][87] A 2018 rapid and specific assay for the detection of MERS-CoV combines the reverse transcription loop-mediated isothermal amplification technique and a vertical flow visualisation strip (RT-LAMP-VF) to detect the nucleocapsid gene of MERS-CoV. 86 The RT-LAMP-VF assay provides detection of MERS-CoV within 35 min and is easier to perform than the WHO-recommended rRT-PCR method.…”
Section: Laboratory Testingmentioning
confidence: 99%
See 1 more Smart Citation
“…84 Several diagnostic tests are under development to accelerate turnaround times from sample analysis to result. [85][86][87] A 2018 rapid and specific assay for the detection of MERS-CoV combines the reverse transcription loop-mediated isothermal amplification technique and a vertical flow visualisation strip (RT-LAMP-VF) to detect the nucleocapsid gene of MERS-CoV. 86 The RT-LAMP-VF assay provides detection of MERS-CoV within 35 min and is easier to perform than the WHO-recommended rRT-PCR method.…”
Section: Laboratory Testingmentioning
confidence: 99%
“…86 Several serological assays are available for detection of MERS-CoV: ELISA, recombinant spike immunofluorescent assay, and spike pseudoparticle neutralisation and microneutralisation assay. [87][88][89][90] A case confirmed by serology requires evidence of seroconversion in two samples, ideally taken at least 14 days apart, by a screening (eg, ELISA, immunofluorescence assay) and a neutralisation assay. 77,78 Imaging A range of abnormal but non-specific chest x-ray findings are seen in patients with MERS.…”
Section: Laboratory Testingmentioning
confidence: 99%
“…36,38 An indirect ELISA has been developed for sero-epidemiological testing and surveillance purposes and requires evaluation in field studies. 39 MERS-CoV testing must be performed in appropriately equipped biosafety laboratories by staff trained in the relevant technical and safety procedures. National or WHO guidelines on laboratory biosafety should be followed in all circumstances.…”
Section: Laboratory Tests For Middle East Respiratory Syndrome Coronamentioning
confidence: 99%
“…In-house indirect MERS-CoV S1 subunit protein based ELISA (rS1-ELISA) was used for the initial screening of MERS-CoV Abs in serum samples as previously described [31]. In brief, 1:400 diluted serum samples were incubated on blocked flat bottom microtiter plates (Thermo Scientific, Rochester, NY) coated with 2 g/ml recombinant MERS-CoV S1 protein (SinoBiological, China) for 1 h at room temperature.…”
Section: Cell Line Virus and Recombinant Proteinmentioning
confidence: 99%
“…Several serological methods have been proven to be valuable in MERS epidemiological studies where screening assays such as ELISA or immunofluorescence should be confirmed by neutralization assays for increased specificity. Here, we used validated recombinant S1-ELISA (rS1-ELISA) [31] combined with neutralization assays to investigate the seroprevalence rate of MERS-CoV in a large cohort of archived sera collected between 2011 and 2016 from healthy blood donors from 50 different nationalities residing in western Saudi Arabia. All samples that tested positive using the rS1-ELISA were confirmed by both MERS-pseudotyped and live virus neutralization assays, and cases that were positive in either neutralization assay were considered confirmed seropositive for MERS antibodies (Abs).…”
Section: Introductionmentioning
confidence: 99%